A dynamic model of the change from pre- to post-aspiration in Andalusian Spanish. (November 2020) - Cronenberg, Johanna; Gubian, Michele; Harrington, Jonathan; Ruch, Hanna
Highlights: Pre- and post-aspiration in Andalusian Spanish /sp, st, sk/ are in a trade-off. The trade-off is predictable from closure timing as found by functional PCA. The trade-off can only be uncovered using time-varying signals, not durations. Sound change confirmed to be further advanced in young West than old East Andalusians. The cognitive-computational model connects exemplar theory with articulatory phonology. Abstract: In Andalusian Spanish, there is a well-documented sound change in which pre- has become post-aspiration in sequences of /s/ followed by voiceless stops. Here we investigate acoustically its synchronic basis across two age groups and two different regions of Andalusia that differ in the degree to which the sound change has advanced. For this purpose, Functional Principal Component Analysis (FPCA) was applied to the probability of voicing and to the degree of closure that had been estimated from the speech signal extending between the two vowels on either side of the aspirated cluster. The first principal component derived from FPCA was mostly associated with changes to the timing of the closure. Earlier closures were characteristic of both younger and West Andalusian speakers and of alveolar stops. In the signals parametrised by the first PC score, post- and pre-aspiration were found to be acoustically inversely related to each other and predictable from closure timing. The general conclusion is that the sound change by which pre- evolves into post-aspiration is a derivative of resynchronising the closure relative to the voiceless interval that emerges after decomposing speech signals varying over a wide range of speakers into principal components of variation.